Factors Influencing the Risk of Early Marriage Among Adolescents at SMPN 5 Panyabungan, Mandailing Natal Regency in 2024 - Wahida Siregar, Rahmi; Batubara, Khoirunnisa; Yanti, Asmima; Harahap, Meilani; Hasibuan, Darma Afni; Pulungan, Nikmatul Khoiriyah (PT Inovasi Pratama Internasional, 2024)
Indonesia is the country with the second highest early marriage rate in the ASEAN after Cambodia. Almost 10% of girls become mothers at the age of 16 in poor and developing countries with the highest rate, one of which is in Southeast Asia. The researcher's aim: to analyze of Factors That Influence Adolescents on the Risk of Early Marriage at SMPN 5 Panyabungan Mandailing Natal Regency 2024. Research method: namely a correlational method, the sample size is 55 people. The instrument used was a questionnaire. The results of the analysis prove that the majority of teenagers with poor knowledge are 27 people (49%), while the minority are teenagers with good knowledge as many as 6 people (10.9%). The results of the research show that there is a relationship between knowledge based on age (pvalue=0.021), and knowledge based on sources of information (pvalue=0.014) for young women regarding maturing marriage age and the risk of early marriage at SMP Negeri 5 Panyabungan, Mandailing Natal Regency. The conclusion of the research results was that there was a relationship between knowledge based on age and knowledge based on information sources for young women regarding early marriage at SMP Negeri 5 Panyabungan, Mandailing Natal Regency in 2024.